Expressão de fatores miogênicos e de microRNAs no músculo esqueléticos de ratos submetidos a estímulo atrófico e recuperação por treinamento físico - Bertaglia, Raquel Santilone [UNESP] (2015)
Understanding the cellular and molecular mechanisms involved in hypertrophy and atrophy processes have been the subject of much research. This fact contributes to development of effective therapeutic strategies to attenuate/block the muscle mass loss. However, myogenic factors and muscle-specific miRNAs have been studied to understand the skeletal muscle adaptive responses. The aim of this study were to evaluate the morphological and functional adaptations, the gene expression of myogenic, anabolic and catabolic factor, and the expression of microRNAs in skeletal muscle of rats submitted to atrophic stimulus followed by physical training. 80 male Wistar rats were used (80 days 250 to 300 g) were divided into 10 groups (n = 8) C: Control; IM: immobilizated; C3: control 3 days; R3: recovered without exercise 3 days; T3: aerobic training 3 days; TF3: strength training 3 days; C7: control 7 days; R7: recovered without exercise 7 days; T7: aerobic training 7 days and TF7: strength training 7 days. Initially, the animals of I, R3, R7, T3, T7, TF3 and TF7 groups were underwent period of hindlimb immobilization by 7 day. Plantaris (Pl - glycolytic and fast twitch) and soleus (Sol - oxidative and slow twitch) muscles were analyzed. Muscle atrophy was confirmed by the analysis of cross-sectional area (CSA) of fibers in groups I and C. The T3 and T7 groups, were underwent a muscle recovery program with aerobic exercise (swimming) 3 period and 7 days respectively while the TF3 and TF7 groups were underwent a muscle recovery program with resistance exercise (jump). At the end of experiment the Pl and Sol muscles were submitted to analysis: morphological, immunohistochemical, biochemical and molecular. Muscle atrophy was observed in both muscles after immobilization, but after 7 days of recovery, only the T7 group showed recovery in CSA. Gene expression data showed: increase in genes involved in muscle atrophy in group I in Sol (MAFbx, PGC-1α and ...